Methods to reduce construction waste and its impact to construction industry / Che Norsyazlina Che Ismail - Che Ismail, Che Norsyazlina (2021)
Generally, construction activity on site can generate large amounts of waste materials that need to be disposed of, known as construction waste. Construction waste includes waste generated during construction activities such as the materials' packaging or the demolition and materials surplus products. Waste in construction will leads to negatively impact the construction project, including increases in the project's cost. However, common issues of construction waste including error design of project, procurement procedure, mismanagement of material storage somehow arise the percentage of waste on site. As the construction waste could contribute to negative impacts in construction works, this study is conducted to identify the methods to reduce the construction waste on site. There were three objectives have been set which are to identify the major factors of increasing construction waste in the construction industry, to investigate the methods of reducing construction waste in the construction industry and to point out the potential impact on reducing waste in the construction industry. A set of questionnaires prepared as the data collection tool to achieve results through selected respondents. Developers, contractors, professionals like the Architect, Engineer, and quantity surveyors were the respondents who have good construction industry knowledge. The outcome of this research includes with potential methods or ways to reduce construction waste to promote a good culture for waste management to achieve sustainable development in the construction industry.